Driving Healthy Behaviors through Social Support: The Role of Co-Responsibility in Weight Loss and Maintenance - Melanie Knufinke-Meyfroyt; Carlo Lancia; Yentl Lodewijks; Simon Nienhuijs; Eva Deckers (Patient Experience Journal)
Objective: The effectiveness of out of hospital lifestyle interventions in healthcare is likely co-dependent on social support from involved one's. We sought to investigate the interrelationships between patient-partner Co-responsibility, Spousal Support, and Self-efficacy and the mechanisms through which they contribute to health behaviors and outcomes relevant to weight loss and maintenance. Methods: Co-responsibility, Spousal Support, self-efficacy, health outcomes and health behaviors like total weight loss, physical activity, OBESI-Q, and health satisfaction were assessed through a questionnaire among 868 individuals attempting to lose weight. Full and semi-partial correlations were used to understand the association between Co-responsibility, Spousal Support, Self-efficacy and health outcomes and behaviors. Results: Results showed that increased Co-responsibility was associated with improved health outcomes and that it extended the construct of Spousal Support. The underlying pathway of associations between Co-responsibility and health outcomes was found to be through Self-efficacy. Finally, it was revealed that increased Co-responsibility caused an improvement in Self-efficacy. Conclusion: Understanding Co-responsibility among patients and their involved one's could provide valuable information to health care professionals to tailor care trajectories and achieve better patient health outcomes.